Integrating the US Military : Race, Gender, and Sexual Orientation since World War II - Stur, Heather Marie, 1975-; Bristol, Douglas Walter, 1965- (Book collections on Project MUSE., 2017)
"Integrating the US Military is an edited collection that examines the US Army's role and place in progressive social change through the lens of the military experience of African Americans, women, and gays since World War II. By making this long overdue comparison, the editors argue this anthology demonstrates how the challenges launched against the racial, gender, and sexual status quo in the years after World War II transformed overarching ideas about power, citizenship, and America's role in the world. This anthology's major contribution is synthesizing recent scholarly work on the history of minorities and women in the US military. It does so by examining connections between GIs and civilian society in the context of ideologies of race, gender, and sexuality. Given the militarization of American society since World War II, revealing the links between these legally marginalized groups within the Armed Services is historically significant in its own right. At the same time, this comparison also sheds new light on a broad range of issues that affected civilian society, such as affirmative action, integration, marriage laws, and sexual harassment. Integrating the US Military is a book designed for college students, military professionals, policy makers, and general readers. Allowing readers to view the history of several civil rights movements within the Armed Forces will prompt them to rethink the way they understand the history of social movements. It will also help them to better understand the relationship between the military and American society. Finally, readers will gain a historical perspective on recent debates about the rights of gays in the military and the implications of deploying women in combat."--Provided by publisher.